If it's not what You are looking for type in the equation solver your own equation and let us solve it.
36-6x+2=30-3x
We move all terms to the left:
36-6x+2-(30-3x)=0
We add all the numbers together, and all the variables
-6x-(-3x+30)+36+2=0
We add all the numbers together, and all the variables
-6x-(-3x+30)+38=0
We get rid of parentheses
-6x+3x-30+38=0
We add all the numbers together, and all the variables
-3x+8=0
We move all terms containing x to the left, all other terms to the right
-3x=-8
x=-8/-3
x=2+2/3
| 12x-30-4x-8=14 | | 4-8x-6-2x=0 | | 9x-6-7x-2=0 | | 6x+15-2x-10=51 | | X^2-4+p=0 | | 0.7×x=2.8 | | 7-x=15-3x | | 2h+3=3h-6 | | 6u=6/7 | | -6=6s | | 13x-28=3x+7 | | (x-40)=(x+40) | | -6=v/3+6 | | 5/u=8/7 | | z8+9=−35 | | x^2-16x+288=0 | | 100x=54 | | 5+y/6+3y=54 | | 9x+19+10x+4=180= | | (x+12)(x+14)=22 | | -v/3=56 | | V(x)=x(28-2x)(22-2x) | | x+4=3√x | | -4(x+2)+1/2=1/2(4x-6)+3 | | 2.5x+15=1.5x-2 | | 2.5r=76 | | 39+x=67 | | 36+x=82 | | 1/3(x+7)-1/2(x+1)=4 | | 1/3(x+7)–1/2(x+1)=4 | | S−1.5x=5.9 | | 23x.4x–1=32 |